2015
DOI: 10.4172/2157-7099.1000323
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic-induced Histological Alterations in Various Organs of Mice

Abstract: Deposition of arsenic in mice through groundwater is well documented but little is known about the histological changes of organs by the metalloid. Present study was designed to evaluate arsenic-induced histological alterations in kidney, liver, thoracic artery and brain of mice which are not well documented yet. Swiss albino male mice were divided into 2 groups and treated as follows: Group 1: control, 2: arsenic (sodium arsenite at 10 mg/kg b.w. orally for 8 wks). Group 2 showed marked degenerative changes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…This procedure demonstrates pretty well every practical histopathologic with additional diagnostic studies such as histological examination in microscopy scission. [18][19][20] …”
Section: Histological Treatmentmentioning
confidence: 99%
“…This procedure demonstrates pretty well every practical histopathologic with additional diagnostic studies such as histological examination in microscopy scission. [18][19][20] …”
Section: Histological Treatmentmentioning
confidence: 99%
“…Histopathology and serum biochemistry serve as an initial indicator of physiological dysfunction and the incidence of liver intoxication [42, 43]. To observe NaAsO 2 -induced liver alterations, we performed histopathology on liver tissues.…”
Section: Discussionmentioning
confidence: 99%
“…The dose and duration of arsenic treatment in vitro can be a critical factor in identifying targets of arsenic toxicity relevant to human exposures. A study found that chronic treatment in mice (8 wk) with high arsenite exposure (150 ppm) resulted in hepatic damage with observed tissue necrosis and significantly elevated serum glutamate-pyruvate transaminase (Noman et al 2015). HepG2 human hepatoma cells have been used as a model to study both the long-and short-term effects of arsenite on insulin signaling.…”
Section: Hepatic Glucose Metabolism and Insulin Signalingmentioning
confidence: 99%
“…The network analyses highlight genes involved in hepatic lipid metabolism and inflammation, such as SIRT1 and sterol regulatory element-binding protein (SREBP) ( Figure 5). The chemical's pronounced effects on liver function, hepatic steatosis, and injury have also been widely reported in murine models (Ditzel et al 2016;Shi et al 2014;Noman et al 2015). However, whether arsenic exposure modulates gluconeogenesis and glycogenolysis in vivo remains unexplored.…”
Section: )mentioning
confidence: 99%